Estimación de las emisiones de CO2 desde la perspectiva de la demanda de transporte en Medellín - Ríos Bedoya, Vanessa (2016)
The transport sector is one of the main actors for emissions of greenhouse gases, these emissions have been increasing in recent decades, reaching values never before achieved despite technological improvements implemented in transportation. This situation requires special attention, especially in developing cities where economic and population growth brings higher levels of car ownership and distances traveled. This paper examines CO2 emissions from the demand point of view of transport in the Metropolitan Area of the Aburrá Valley (AMVA) and Medellín. The data for this survey were used EOD2012 daily mobility. The results allowed to know how the variables related to travel, socioeconomic and territorial variables contribute to CO2 emissions. In addition, a CHAID decision tree was used to observe how socioeconomic factors affect the decision to use a mean of transport more contaminating than others, realizing the close relationship between income and CO2 emissions by transport use.